Early warnings of the transition to a superrotating atmospheric state - M. S. Williamson; M. S. Williamson; T. M. Lenton (Earth System Dynamics)
Several general circulation models (GCMs) show bifurcations of their atmospheric state under a broad range of warm climates. These include some of the more extreme global warming scenarios. This bifurcation can cause the transition to a superrotating state, a state where its angular momentum exceeds the solid body rotation of the planet. Here we use an idealised GCM to simulate this transition by altering a single non-dimensional control parameter, the thermal Rossby number. For a bifurcation-induced transition there is potential for early warnings, and we look for these here. Typically used early warning indicators, variance and lag-1 autocorrelation, calculated for the mean zonal equatorial wind speed, increase and peak just before the transition. The full autocorrelation function taken at multiple lags is also oscillatory, with a period of 25 d preceding the transition. This oscillatory behaviour is reminiscent of a local supercritical Hopf bifurcation. Motivated by this extra structure, we use a generalised early warning vector technique based on principal oscillation patterns (POPs) to diagnose the dominant spatial modes of the horizontal wind field fluctuations. We find a zonal-wavenumber-0 pattern that we call the “precursor” mode that appears shortly before and disappears soon after the transition. We attribute the increase in the early warning indicators to this spatial precursor mode. This mode is correlated to oscillations in strength of the Hadley cells. Following the transition, an eastward-propagating zonal-wavenumber-1 mode of period ∼4 d dominates the dynamics. This mode appears to be representative of the Kelvin–Rossby instability others have previously identified. Although the control parameter used to simulate the transition is unlikely to be relevant to future climate change, the Kelvin–Rossby transition mechanism may well be relevant, and the simulations reported here do show early warnings and serve as a test bed for whether we can detect this transition before it happens.